Reaganomics and the world economy - Günter Großer; Günter Weinert (Intereconomics, 1984)
The upswing in the US economy, which has long since surpassed all expectations, has undoubtedly been a great success for the economic policy embarked upon by President Reagan. But has the treatment which has done the USA so much good also been good for the rest of the world? American observers always draw attention to the import boom, whilst overseas commentators are more concerned with the worldwide effects of the USA's very high interest rates.
Keywords: 330; USA